Production of mead flavored with black garlic (Research, Society and Development, 2020)
The objective of the present work was to elaborate mead with and without the addition of black garlic in the maturation stage and to evaluate its physicochemical characteristics. The must was obtained by diluting the honey in sterile mineral water until it reached 24ºBrix, then pasteurized at 65°C for 30 minutes. The inoculum was prepared using beer yeast Sacharomyces cerevisae. Fermentation was carried out at 20°C, clarification by gravity, pasteurization and maturation for 180 days at 7ºC. The treatment samples were analyzed for pH, total soluble solids content, total acidity, reduced dry extract and alcoholic strength. The experiment was conducted in a completely randomized design, consisting of two treatments (without and with the addition of 1% black garlic in the maturation stage) and two replications. The collected data were submitted to analysis of variance using the F test at a significance level of 5%. It was verified that all the physicochemical parameters evaluated for the produced meads are in conformity with the current Brazilian legislation and that the meads fall into the category and are smooth and full-bodied. Of the parameters evaluated, only the total acidity showed a statistical difference between the produced meads.